Procedural specificity in laparoscopic simulator training: protocol for a randomised educational superiority trial - Bjerrum, Flemming (BioMed Central, 2014)
BACKGROUND: The use of structured curricula for minimally invasive surgery training is becoming increasingly popular. However, many laparoscopic training programs still use basic skills and isolated task training, despite increasing evidence to support the use of training models with higher functional resemblance, such as whole procedural modules. In contrast to basic skills training, procedural training involves several cognitive skills such as elements of planning, movement integration, and how to avoid adverse events. The objective of this trial is to investigate the specificity of procedural practice in laparoscopic simulator training. METHODS/DESIGN: A randomised single-centre educational superiority trial. Participants are 96 surgical novices (medical students) without prior laparoscopic experience. Participants start by practicing a series of basic skills tasks to a predefined proficiency level on a virtual reality laparoscopy simulator. Upon reaching proficiency, the participants are randomised to either the intervention group, which practices two procedures (an appendectomy followed by a salpingectomy) or to the control group, practicing only one procedure (a salpingectomy) on the simulator. 1:1 central randomisation is used and participants are stratified by sex and time to complete the basic skills. Data collection is done at a surgical skills centre. The primary outcome is the number of repetitions required to reach a predefined proficiency level on the salpingectomy module. The secondary outcome is the total training time to proficiency. The improvement in motor skills and effect on cognitive load are also explored. DISCUSSION: The results of this trial might provide new knowledge on how the technical part of surgical training curricula should be comprised in the future. To examine the specificity of practice in procedural simulator training is of great importance in order to develop more comprehensive surgical curricula. TRIAL REGISTRATION: ClinicalTrials.gov: NCT02069951